Academic Stress and Mental Well-Being in College Students: Correlations, Affected Groups, and COVID-19 - Barbayannis, Georgia; Bandari, Mahindra; Zheng, Xiang; Baquerizo, Humberto; Pecor, Keith W.; Ming, Xue (Frontiers in Psychology, 2022)
Academic stress may be a dominant stressor that affects college students' mental well-being. Some groups of students may experience more stress than others, and the coronavirus disease 19 (COVID-19) pandemic could further complicate the stress. We surveyed 843 college students and evaluated whether academic stress levels affected their mental health and, if so, whether there were specific vulnerable groups by gender, race/ethnicity, year of study, and reaction to the pandemic. Using a combination of scores from the Perception of Academic Stress Scale (PAS) and the Short Warwick-Edinburgh Mental Well-Being Scale (SWEMWBS), we found a significant correlation between worse academic stress and poorer mental well-being in all students, who also reported an exacerbation of stress in response to the pandemic. In addition, SWEMWBS scores revealed the lowest mental health and highest academic stress in nonbinary individuals and the opposite trend for both measures in males. Furthermore, females and nonbinary students reported higher academic stress than those reported in males, as indicated by PAS scores. The same pattern held as a reaction to COVID-19-related stress. PAS scores and responses to the pandemic varied among year of study, but no obvious patterns emerged. These results indicate that academic stress in college is significantly correlated to psychological well-being in the students who responded to this survey. In addition, some groups of college students are more affected by stress than others, and additional resources and support should be offered to them.